Population biology of Trichomycterus sp. (Siluriformes, Trichomycteridae) in Passa Cinco stream, Corumbataí River sub-basin, São Paulo State, southeastern Brazil - Rondineli,GR. (2009)
The aim of this work was to characterise the population of Trichomycterus sp. in Passa Cinco stream, regarding length structure, sex ratio, diet and reproductive aspects, in accordance with drought and rainy season periods and longitudinal gradient, as well as to analyse its corporal condition in a temporal dimension. Six samplings were accomplished with the use of electric fishing equipment in three different sites in Passa Cinco stream, contemplating sites of order two, three and four, during the months of May, July, September and November of 2005; and January and March of 2006. Three hundred and forty one individuals were captured, composed of 203 males, 99 females and 39 immatures. The smallest captured individual, an immature, presented 28 mm of standard length and the largest, a male, 85 mm. There was not significant variation in repletion degree and accumulated fat in the visceral cavity of the individuals analysed during the considered periods. Eleven different food items were found in the stomach contents. Considering the whole sampling period, immature Diptera was a preferential item and other items were found as occasionally ingested. Spearman and Friedman tests did not find significant differences in the diet of Trichomycterus sp. in the periods and sampling sites, respectively. The average of absolute fecundity was of 73 oocytes, and the parceled type of spawning was performed. Both males and females of Trichomycterus sp. presented significant differences in their corporal conditions in the considered periods, and in the rainy season, these fishes were in better condition.